Bridging Artistic Traditions - Enriching Metalwork and Jewelry through Islamic Art Patterns and Etching Acid Technique (Al-Academy, 2024)
This research examines the potential of incorporating Islamic art patterns into contemporary metalwork and jewelry using the etching acid technique. It emphasizes the enduring historical and cultural value of these art patterns, which are deeply rooted in the Islamic faith and culture. The significance goes beyond aesthetics, fostering spiritual connections. The review of existing works highlights how these patterns have influenced modern art, architecture, and diverse design fields, showcasing their continued relevance. Additionally, it explores the benefits of using acid etching in jewelry making, emphasizing precision, complexity, and the preservation of spiritual and cultural symbolism associated with Islamic art. The objectives of this study align with its findings by emphasizing the importance of historical context, possibilities for integration, effects of Islamic art patterns, and their impact on innovative metalwork and jewelry designs. This paper lays the foundation for empirical investigations by highlighting the potential to harmoniously blend tradition and modernity.